Nanopartículas de grafite para carreamento de antiinflamatórios não esteroidais por estudos de docking molecular - Leves, Natalia (2013)
The non steroidal anti-inflammatory drugs have been known for over 100 years and has been widely used by mankind. However cause adverse effects, since gastrointestinal complications to cardiac diseases many of these symptoms related to its nonspecific action in biological systems. Thus, the proposal of a drug delivery system for loading these drugs to the site of inflammation, could reduce these unwanted effects in the body due to the limitation of more targeted effects beyond its site of action.In this study, the graphene and graphite plates were used as carriers, since studies demonstrate the usefulness of other conformational structures of carbon as drug carriers for the treatment of cancer, for example. Two models were studied for the plates by softwares of molecular docking: template sandwich, which comprises two carbon plates, with ligant between them, and the model surfing with one carbon plate comprising the ligant. The compounds were obtained from data banks, such as CSD, PDB and SD, the plates were obtained by molecular modeling. The analysis of intermolecular interactions, essential knowledge for understanding the structures obtained was done using molecular imaging with high resolution. The experimental results showed that the in silico model sandwich was the most favorable for this system, providing stability and protection for the ligand that this does not become detached from the plates during the path taken in the body to the desired location.